2020
DOI: 10.1016/j.heliyon.2020.e04356
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of smallholder farmers' adoption of adaptation strategies to climate change in Eastern Tigray National Regional State of Ethiopia

Abstract: Climate change has been significantly affecting smallholder farmer's livelihood and food security. However, efforts to support farmer adaptation are hampered by the lack of scientific and context based evidences. Hence, this paper identified the major adaptation strategies to climate change (CC) and analysed the determinants of adoption of adaptation strategies to climate change in Eastern Tigray Region of Ethiopia. Three-stage sampling technique was used to select the study sites and sample households. Copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 20 publications
7
64
0
1
Order By: Relevance
“…From the findings, farmers with formal education where of the view that climate change can be tackled and this could be because attaining formal education enhances farmers' options to adapt to climate change. This is consistent with the study conducted by Gebru et al (2020) which discovered that farmer's education has a positive and significant influence on adoption of various climate change strategies such as crop varieties, diversification and soil and water conservation. Furthermore, farmers with higher educational level were found to be in a better position to adapt to climate change due to their knowledge and ability to access information on climate change and adaptation options (Ndamani & Watanabe, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…From the findings, farmers with formal education where of the view that climate change can be tackled and this could be because attaining formal education enhances farmers' options to adapt to climate change. This is consistent with the study conducted by Gebru et al (2020) which discovered that farmer's education has a positive and significant influence on adoption of various climate change strategies such as crop varieties, diversification and soil and water conservation. Furthermore, farmers with higher educational level were found to be in a better position to adapt to climate change due to their knowledge and ability to access information on climate change and adaptation options (Ndamani & Watanabe, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Existing empirical studies listed the most used adaptation strategies in African nations such as improved crop varieties, planting trees, soil conservation, changing planting dates and irrigation (Gwambene et al, 2015;Gebru et al, 2020). Several other studies (Bhatt et al 2014;Chapagain et al 2017;Devkota et al 2017;Dhakal et al 2016;Sujakhu et al 2016) have reported that climate change is a threat to agricultural production and sustainability due to the projected variability in temperature and precipitation, and more recurrent droughts, and it is, hence, necessary to study the associated indicators and determinants of farmers choice of adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation result shows that age has a non-significant effect on farmer's perception toward climate change both in Switzerland and Ghana. Several studies show that age significantly affects farmers' perception of climate change (Adzawla et al, 2019;Gebru et al, 2020). Furthermore, Koutsou et al (2014) stated that young farmers have a better perception and adaptation to climate change.…”
Section: Agementioning
confidence: 99%
“…Farmers' perceptions of climate change are among the fundamental drivers that drive farmers to implement autonomous adaptation. For example, farmers' perceptions significantly affect farmers' adaptation to climate change in Saesietsaeda Emba, Ethiopia (Gebru et al, 2020). Also, farmers' perceptions of climate affect the form of adaptation carried out by wheat farmers in Uttar Pradesh, India (Singh, 2020).…”
Section: Introductionmentioning
confidence: 99%